Amphibian (Xenopus laevis) Interleukin-8 (CXCL8): A Perspective on the Evolutionary Divergence of Granulocyte Chemotaxis - Koubourli, Daphne V.; Yaparla, Amulya; Popovic, Milan; Grayfer, Leon (Frontiers in Immunology, 2018)
The glutamic acid-leucine-arginine (ELR) motif is a hallmark feature shared by mammalian inflammatory CXC chemokines such the granulocyte chemo-attractant CXCL8 (interleukin-8, IL-8). By contrast most teleost fish inflammatory chemokines lack this motif. Interestingly, the amphibian Xenopus laevis encodes multiple isoforms of CXCL8, one of which (CXCL8a) possesses an ELR motif, while another (CXCL8b) does not. These CXCL8 isoforms exhibit distinct expression patterns during frog development and following immune challenge of animals and primary myeloid cultures. To define potential functional differences between these X. laevis CXCL8 chemokines, we produced them in recombinant form (rCXCL8a and rCXCL8b) and performed dose-response chemotaxis assays. Our results indicate that compared to rCXCL8b, rCXCL8a is a significantly more potent chemo-attractant of in vivo-derived tadpole granulocytes and of in vitro-differentiated frog bone marrow granulocytes. The mammalian CXCL8 mediates its effects through two distinct chemokine receptors, CXCR1 and CXCR2 and our pharmacological inhibition of these receptors in frog granulocytes indicates that the X. laevis CXCL8a and CXCL8b both chemoattract tadpole and adult frog granulocytes by engaging CXCR1 and CXCR2. To delineate which frog cells are recruited by CXCL8a and CXCL8b in vivo, we injected tadpoles and adult frogs intraperitoneally with rCXCL8a or rCXCL8b and recovered the accumulated cells by lavage. Our transcriptional and cytological analyses of these tadpole and adult frog peritoneal exudates indicate that they are comprised predominantly of granulocytes. Interestingly, the granulocytes recruited into the tadpole, but not adult frog peritonea by rCXCL8b, express significantly greater levels of several pan immunosuppressive genes.